Giant fluctuations at a granular phase separation threshold - Meerson, Baruch; Pöschel, Thorsten; Sasorov, Pavel V.; Schwager, Thomas (Physical Review E, 2004)
The phase separation instability that occurs in a system of nearly elastically colliding hard spheres driven by a thermal wall was investigated. It was demonstrated that if the aspect ratio of the confining box exceeded a threshold value the phase separation could be predicted by granular hydrostatics. It was found that in a wide region of aspect ratios around the threshold, the system was dominated by fluctuations. The two possible scenarios of the origin of the giant fluctuations were also discussed.